Relationship between excessive daily sleepy and quality of life in military firefighters (Research, Society and Development, 2020)
Objective: To relate excessive daytime sleepiness and quality of life in military firefighters. Method: quantitative, transversal research, carried out with 129 military firefighters working in Rio Grande do Sul, who had been performing operational and administrative assistance for more than six months in the function. For the data collection, a sociolaboral and lifestyle questionnaire, Epworth Sleepiness Scale and the World Health Organization Qualityof Life were used. Data were analyzed using descriptive and analytical statistics. Results: Firefighters predominated with no sleepiness and a good general perception of quality of life. An association was identified between drowsiness and the child variables (p = 0.044), experienced risk at work (p